Potential of container terminal operations for RoRo terminals - Stephan Krüger; Marius Marius Schulze; Carlos Jahn (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: With the increasing environmental pollution due to the growing freight transportation, the roll-on roll-off (RoRo) transport is considered one of the most promising alternatives in short sea shipping to the dominant pure road transport. The interruption of the transport chain by freight handling represents a potential for improvement. Therefore, the handling processes at the RoRo terminals, in particular, must be optimized to increase competitiveness. Methodology: A systematic literature review is applied to identify innovative approaches for container terminals to increase terminal efficiency. Gained insights will be examined concerning their transferability to RoRo terminal processes. Findings: The research identified various novel optimization approaches for the functional areas of truck operations, gate-system, storage, transportation, and quay operations. The gate system is the most critical functional area with tremendous potential for improvement; measures based on the optimization approaches are developed. Originality: Based on highly efficient container terminals, optimization potentials for RoRo terminals are identified. This approach has not been pursued before and offers many research opportunities.
urn:nbn:de:gbv:830-882.0200795; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Port Logistics